Improving midwifery curriculum in Indonesia through evidence-based practice integration: Scoping review - Fatimah Azzahra; Ari Indra Susanti (Curricula: Journal of Curriculum Development, 2025)
Midwifery education in Indonesia plays a crucial role in enhancing maternal and neonatal health outcomes. However, several structural challenges hinder its effectiveness. Integrating Evidence-Based Practice (EBP) into midwifery curricula is crucial for addressing these challenges, as it ensures that clinical decisions are grounded in the best available evidence, ultimately enhancing the quality of care provided to mothers and newborns. The study aims to identify challenges and opportunities in incorporating EBP into midwifery education, with a focus on clinical education gaps, institutional support, and resource limitations. This study used a systematic review methodology, conducting a comprehensive search through Google Scholar, PubMed, and ScienceDirect, and analyzing 11 relevant studies. The Findings emphasize the need for enhanced training of teachers and mentors in EBP, addressing competency gaps between theoretical knowledge and clinical practice, and incorporating digital technologies and simulation-based learning to improve EBP competencies among students. The review concludes that a more systematic integration of EBP into midwifery curricula is crucial for enhancing professional practice and achieving Indonesia’s Sustainable Development Goals (SDGs) for maternal health.   Abstrak Pendidikan kebidanan di Indonesia memegang peranan penting dalam meningkatkan hasil kesehatan ibu dan neonatus, namun efektivitasnya terbatas oleh berbagai tantangan struktural. Integrasi Evidence-Based Practice (EBP) ke dalam kurikulum kebidanan sangat penting untuk mengatasi tantangan ini, karena memastikan bahwa keputusan klinis didasarkan pada bukti terbaik yang tersedia, yang pada akhirnya akan meningkatkan kualitas perawatan yang diberikan kepada ibu dan bayi baru lahir. Penelitian ini bertujuan untuk mengidentifikasi tantangan dan peluang dalam mengintegrasikan EBP ke dalam pendidikan kebidanan, dengan fokus pada kesenjangan pendidikan klinis, dukungan institusional, dan keterbatasan sumber daya. Penelitian ini menggunakan metodologi tinjauan sistematik, melakukan pencarian komprehensif melalui Google Scholar, PubMed, dan ScienceDirect, serta menganalisis 11 studi yang relevan. Temuan penelitian menekankan perlunya pelatihan yang lebih baik bagi pengajar dan mentor dalam EBP, mengatasi kesenjangan kompetensi antara pengetahuan teoretis dan praktik klinis, serta mengintegrasikan teknologi digital dan pembelajaran berbasis simulasi untuk meningkatkan kompetensi EBP di kalangan mahasiswa. Tinjauan ini menyimpulkan bahwa integrasi EBP yang lebih sistematis ke dalam kurikulum kebidanan sangat penting untuk meningkatkan praktik profesional dan mencapai SDGs Indonesia dalam kesehatan maternal. Kata Kunci: kebidanan; kurikulum; praktik berbasis bukti